A Novel Brighter Bioluminescent Fusion Protein Based on ZZ Domain and Amydetes vivianii Firefly Luciferase for Immunoassays - Viviani, Vadim R.; Silva, Jaqueline Rodrigues; Ho, Paulo Lee (Frontiers in Bioengineering and Biotechnology, 2021)
Immunoassays are widely used for detection of antibodies against specific antigens in diagnosis, as well as in electrophoretic techniques such as Western Blotting. They usually rely on colorimetric, fluorescent or chemiluminescent methods for detection. Whereas the chemiluminescence methodsare more sensitiveand widely used, they usually suffer of fast luminescence decay. Here we constructed a novel bioluminescent fusion protein based on the N-terminal ZZ portion of protein A and the brighter green-blue emitting Amydetesvivianiifirefly luciferase. In the presence of D-luciferin/ATP assay solution, the new fusion protein, displays higher bioluminescence activity, is very thermostable and produces a sustained emission (t1/2>130min). In dot blots, we could successfully detect rabbit IgG against firefly luciferases, Limpet Haemocyanin, HRP and SARS-Covid-19 Nucleoprotein (1-250 ng), as well as the antigen bound antibodiesusing either CCD imaging or photography. Using CCD imaging we could detect less than 1 ng of SARS-COVID-19 Nucleoprotein. Using this system, we could also successfully detect firefly luciferase and SARS-COVID nucleoprotein in Western Blots (5-250 ng). Comparatively, the new fusion protein displays similar or higher and more sustained luminescent signal when compared to commercial HRP-labeled secondary antibodies, constituting a novel promising alternative for Western Blotting and immunoassays.